The impact of the fall of the Second French Empire in 1870 on local sheikhdoms in Algeria - "The Sheikhdom of Majana as a model" - sammari, boubaker; laib, hiba (Journal of Social Sciences and Humanities, 2025)
The concept of local chieftaincies (Mashiakhat) evolved as an administrative institution for the tribal domain across different periods, based on the characteristic of hereditary succession and the tribal organization loyal to the ruling power. From this standpoint, this study attempts to shed light on an example of these chieftaincies: the Mijana Chieftaincy (Mashiakhat Majana). The roots of this chieftaincy trace back to the Qalaa of Beni Abbas (Kalâa des Beni Abbès), the Emirate of Awlad Muqran (Ouled Mokrane), one of the great influential families that held significant roles during the Ottoman period. This family also interacted with the French colonial administration, particularly during the period of the Second French Empire (1852–1870), before its social cornerstone, the "Muqrani family," was subjected to dismantling and fragmentation in the context of abolishing the system of the Arab Bureaus (Bureaux Arabes) and the emergence of the civil system. The study aims to demonstrate the repercussions of the fall of the Second French Empire in 1870 on the local chieftaincies in Algeria, taking the Mijana Chieftaincy as an example. It will examine the consequences and effects resulting from the colonial administration's resort to the displacement of the Hachem tribes and the settlement of colonists from Alsace and Lorraine. This led to changes in the social and economic structure of the region's inhabitants and the Mijana Chieftaincy, employing a historical, analytical, and comparative methodology.